Pharmacokinetics and Bioequivalence of Two Norfloxacin Oral Dosage Forms (Vapcotril - 10%® and Mycomas 10%®) in Healthy Broiler Chickens - Abu-Basha, Ehab A.; Gharaibeh, Saad M.; Abudabos, Alaeldein M.; Shunnaq, Ahmad F.; Al-Majali, Ahmad M. (International Journal of Poultry Science, 2008)
A pharmacokinetic and bioequivalence evaluation of two norfloxacin oral solutions was carried out in healthy broiler chickens after oral administration according to a single dose, randomized, parallel-experimental design. The two formulations were: Vapcotril-10%® (Vapco, Jordan) as a test product and Mycomas 10%® (Univet, Ireland) as a reference product. The chickens were allotted into 3 equal groups (8 chickens/group). Chickens of group 1 and 2 were given a single oral dose of Vapcotril-10%® and Mycomas 10%® at a dose level of 16 mg/kg body weight (bw), respectively after an overnight fasting. Chickens of group 3 were given a single intravenous dose of norfloxacin to calculate the systemic bioavailability. Serial blood samples were collected from the left brachial or cutaneous ulnar veins at different time points post drug administration. Norfloxacin concentrations in chicken plasma were determined using a microbiological assay and Klebsiella pneumoniae ATCC 10031 as a test organism. The pharmacokinetics analysis of the data was performed using non-compartmental analysis based on statistical moment theory (SMT) with the help of computerized WinNonlin program (Version 5.2, Pharsight, CA, USA). The maximum plasma concentration (Cmax), time to reach peak concentration (tmax), area under plasma concentration-time curve (AUC0-12h and AUC0-inf), elimination half-life (t1/2beta) and systemic bioavailability (F) were. 4.94 ± 0.06 and 3.88 ± 0.07 μg/ml, 1.0 and 2.0 h, 21.60 ± 0.54 and 20.51 ± 0.39 μg.h/ml, 25.40 ± 0.76 and 23.40 ± 0.69 μg.h/ml, 4.49±0.13 and 3.87±0.21h, 50 and 47.5% for Vapcotril-10%® and Mycomas 10%®, respectively. The 90% confidence interval for test: reference ratio of the AUC0-12h (99.53-111.15), AUC0-inf (100.9-116.72) and Cmax (122.69-132.15) was within the EMEA bioequivalence acceptance range of 80%–125% for the AUC and 75-133 for the Cmax. In conclusion, Vapcotril-10%® is bioequivalent to Mycomas 10%® and can be used as interchangeable therapeutic agents in veterinary medicine practice.